2009
DOI: 10.14710/jitaa.34.4.253-257
|View full text |Cite
|
Sign up to set email alerts
|

AMINO ACID PROFILE OF EARTHWORM AND EARTHWORM MEAL (Lumbricus rubellus) FOR ANIMAL FEEDSTUFF

Abstract: Earthworm meal (Lumbricus rubellus) has become one of natural material that could be used as feed additive. Powdering method of earthworm was done by using formic acid addition. The study was carried out (1) to evaluate the essential amino acid profile of earthworm and earthworm meal, (2) to calculate the value of essential amino acid index (EAAI) of both materials. A modified EAAI equation was developed from the essential amino acid profile of earthworm and earthworm meal. The result showed that essential ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 14 publications
0
43
2
7
Order By: Relevance
“…In addition, the same authors found that the EAAs composition (g/16 gN) for the EW they analyzed as arg (2.83%), hist (1.47%), isoleu (2.04%), leu (4.11%), lys (6.35%), meth (5.30%), phy (6.26%), thr (4.43%) and val (4.43%). Istiqomah et al (2009) reported that proximate analysis of earthworm meal on DM basis (EWM; Powdering method of EW was done by using 3% formic acid addition) was found as 63.06% CP, 18.5% EE, 0.19% CF, 12.41% NFE and 5.81% ash. They also compared the EAAs profile of EW and EWM.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…In addition, the same authors found that the EAAs composition (g/16 gN) for the EW they analyzed as arg (2.83%), hist (1.47%), isoleu (2.04%), leu (4.11%), lys (6.35%), meth (5.30%), phy (6.26%), thr (4.43%) and val (4.43%). Istiqomah et al (2009) reported that proximate analysis of earthworm meal on DM basis (EWM; Powdering method of EW was done by using 3% formic acid addition) was found as 63.06% CP, 18.5% EE, 0.19% CF, 12.41% NFE and 5.81% ash. They also compared the EAAs profile of EW and EWM.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Since Lawrence and Miller irst reported the protein content of earthworm in 1945, many nutritional evaluations of the earthworm have been published [14][15][16][17][18][19][20][21]. From the literature, it can be concluded that earthworms contain high levels of protein and that this protein is rich in the amino acids, considered essential for food of domesticated animals and humans.…”
Section: Amino Acidmentioning
confidence: 99%
“…The earthworms were dried using an oven set at 50 0 C 10 hours according to the method described by Istiqomah at al. [10]. After drying, the worms were weighed, then milled with a hammer milling machine into a powdered form.…”
Section: Broiler Feedmentioning
confidence: 99%
“…The dominant essential amino acid in fresh earthworms was histidin and in earthworm meal isoleucine [10]. Among the non-essential amino acids the most common was glutamic acid both in fresh earthworms and earthworm meal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation